1962
DOI: 10.1677/joe.0.0240053
|View full text |Cite
|
Sign up to set email alerts
|

The Pituitary Gland of Normal and Stalk-Sectioned Monkeys With Particular Reference to the Pars Intermedia

Abstract: The pars distalis, pars intermedia and infundibular process make up, respectively, 61, 5 and 34% of the volume of the pituitary gland of normal mature female rhesus monkeys. The pars distalis is relatively smaller in immature animals, and larger during pregnancy.Section of the pituitary stalk is followed by a significant increase in the volume of the pars intermedia; the infundibular process always decreases in volume, while the pars distalis shrinks to a lesser and more variable extent.Histological changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1963
1963
1973
1973

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…[1963a, b]. However, Holmes [1962] found that section of the hypophysial stalk in rhesus monkeys caused a significant increase in the volume of the pars intermedia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1963a, b]. However, Holmes [1962] found that section of the hypophysial stalk in rhesus monkeys caused a significant increase in the volume of the pars intermedia.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some evidence of a relationship between the pars intermedia and the hypo thalamus. Hypertrophy of the pars intermedia has been observed following stalk transection in rabbits [Brooks, 1938], rats [Barrnett and G reep, 1951], goats [Daniel and P richard, 1958;A dams et al, 1966], and in monkeys [Holmes, 1962], although it has also been reported not to occur in rabbits [Campbell and Harris, 1957]. The above observations were made on mature animals.…”
mentioning
confidence: 98%
“…In assessing the merits of this particular operation as a means of depressing pituitary function, it is important to know the extent to which the structure of the gland is altered and its functions impaired. There are few reports in the literature on the effects of stalk section on the human pituitary (Dandy and Goetsch, 1911;Russell, 1956; Daniel, Prichard, and Schurr, 1958;Le Beau and Foncin, 1960;Nicolaidis, 1962; Adams, Daniel, Prichard, and Schurr, 1963), although much information has now been obtained on the effects of the operation on several species of animal (Harris, 1950;Barrnett and Greep, 1951;Greep and Barrnett, 1951;Benoit and Assenmacher, 1953;Campbell and Harris, 1957;Daniel and Prichard, 1958;Holmes, 1961Holmes, , 1962 Laszlo, David, and Kovics, 1962; Adams, Daniel, and Prichard, 1963a, b, c; 1964a, b, c; 1966a, b; Jacobsohn, 1966). We have now had the opportunity of examining the glands of 21 human patients surviving for various periods of time after stalk section and in this paper we report our findings in these pituitary glands.…”
mentioning
confidence: 99%
“…Holmes, however, found that pars intermedia became thicker than normal in ferrets which survived 6 weeks to 5-months after operation; it appeared as a folded mass of cells surrounding a small core of neuro-hypophysial tissue. More recently, Holmes [1962] made measurements in the monkey, and reported that pars intermedia increased in size after stalk section.…”
Section: Discussionmentioning
confidence: 99%